On the Crossing Number of Kn without Computer Assistance. Issue 4 (1st October 2015) - McQuillan, Dan; Richter, R. Bruce
Abstract: We present several general results about drawings of K n, as a beginning to trying to determine its crossing number. As application, we give a complete proof that the crossing number of K 9 is 36 and that all drawings in one large, natural class of drawings of K 11 have at least 100 crossings.